Leadership of Madrasah Heads in Improving the Quality of Educational Institutions (Case Study at MAN 2 Malang City) - Zaini, Mohammad (CV. Inara, 2024)
Determine and analyze the leadership of madrasa heads in improving the quality of educational institutions in MAN 2 Malang City. The research method used is a qualitative research method with a phenomenological research type. Data collection techniques are interviews, observation and documentation. Data analysis by condensing data, presenting data and drawing conclusions/verification. The results of the research: 1) the head of the madrasah in mobilizing to improve the quality of educational institutions in MAN 2 Malang City was carried out by; participate in preparing lesson plans, select teachers who are competent in guiding students in self-development, provide motivation to subordinates, form team work (cooperation), coordinate task activities for participating in training, the head of the madrasah also holds meetings with subordinates, and provide motivation to subordinates by setting a good example. 2) The leadership of the madrasa head in directing improving the quality of educational institutions in MAN 2 Malang City is carried out by; the head of the madrasah motivates teachers to be more creative, and coordinates the results of their work, the head of the madrasah always evaluates teacher activities, and holds official meetings with subordinates, by providing motivation to teachers during official meetings, the head of the madrasah gives a task for teachers to take part in training, the head of the madrasah gives the teacher the task of making lesson plans, the head of the madrasah also sets a good example for his subordinates to be an example of hard work for his subordinates. 3) The leadership of the madrasah head in influencing the improvement of the quality of educational institutions in MAN 2 Malang City is carried out by the madrasah head giving awards to teachers who excel in guiding students, the madrasah head providing role models and providing attention, providing welfare, setting a good example well, providing motivation to subordinates, the head of the madrasah supports and gives appreciation to the achievements of his subordinates.